Identification of bromodomain-containing proteins prognostic value and expression significance based on a genomic landscape analysis of ovarian serous cystadenocarcinoma - Zhang, Juan; Li, Yan; Fan, Ting-yu; Liu, Dan; Zou, Wen-da; Li, Hui; Li, Yu-kun (Frontiers in Oncology, 2022)
Abstract Background: Ovarian serous cystadenocarcinoma (OSC), a common gynaecologic tumour, is characterized by high mortality worldwide. Bromodomain (BRD)-containing proteins are a series of evolutionarily conserved proteins that bind to acetylated Lys residues of histones to regulate the transcription of multiple genes. The ectopic expression of BRDs is often observed in multiple cancer types, but the role of BRDs in OSC is still unclear. Methods: We performed the differential expression, GO enrichment, GSEA, immune infiltration, risk model, subtype classification, stemness feature, DNA alteration, and epigenetic modification analysis for these BRDs based on multiple public databases. Results: Most BRDs were dysregulated in OSC tissues compared to normal ovary tissues. These BRDs were positively correlated with each other in OSC patients. Gene alteration and epigenetic modification were significant for the dysregulation of BRDs in OSC patients. GO enrichment suggested that BRDs played key roles in histone acetylation, viral carcinogenesis, and transcription coactivator activity. Two molecular subtypes were classified by BRDs for OSC, which were significantly correlated with stemness features, m6A methylation, ferroptosis, drug sensitivity, and immune infiltration. The risk model constructed by LASSO regression with BRDs performed moderately well in prognostic predictions for OSC patients. Moreover, BRPF1 plays a significant role in these BRDs for the development and progression of OSC patients. Conclusion: BRDs are potential targets and biomarkers for OSC patients, especially BRPF1.